Cholestatic Hepatitis in Graves' Disease: A Diagnostic Challenge. Issue 1 (14th January 2021) - Haddaden, Metri; Hanna, Angy; Odish, Fadi; Husami, Samir; Imam, Zaid; Tahhan, Mamon
ABSTRACT: Cholestatic hepatitis is a rare presentation of thyrotoxicosis potentially confused as an adverse effect of antithyroid therapy. We report a 37-year-old man with cholestatic hepatitis as an initial presentation of Graves' disease. Diagnostic evaluation demonstrated (i) elevated transaminases and alkaline phosphatase (R-factor value: 2.6), and marked cholestasis (total bilirubin: 17.3 mg/dL, direct bilirubin: 9.4 mg/dL); (ii) negative hepatitis, viral, and autoimmune serologies; (iii) normal magnetic resonance cholangiopancreatography; (iv) liver biopsy with marked cholestasis and no fibrosis; (v) thyroid-stimulating hormone <0.01, fT4 (free thyroxine): 1.5, fT4 (free triiodothyronine): 4.3 and positive thyroid-stimulating immunoglobulins. Radioiodine uptake scan confirmed Graves' disease. Clinical resolution was achieved with propranolol, prednisone, methimazole, and thyroidectomy.